Dimensions of intonation. Wiktor Jassem’s contribution to the studies on the melody of speech - Karpiński, Maciej (Lingua Posnaniensis, 2016)
Intonation is often considered the most problematic component of prosody. It may largely contribute to the meaning of an utterance and provide rich indexical information. The complexity of the intonationrelated phenomena, from the acoustic level up to the cognitive process of semiosis, resulted in a variety of conceptualisations and divergent theoretical approaches. In the present text, an attempt is made to sketch the late Wiktor Jassem’s contribution to intonation studies, starting from his early work on colloquial British English to the studies focused on the Polish language as well as his general perspective on prosody and on the methods of its exploration. Some of his unpublished contribution to research projects on various aspects of prosody is also acknowledged. The present overview is based both on available written materials (publications, references, reports, reviews) and the author’s personal communication with Wiktor Jassem and his collaborators.